Description of Patient Acceptance of Use of Mask by Doctor at Poly Out-Patient Care Puskesmas, Bantul - Wahyu Pamungkasih; Adi Heru Sutomo; Mahar Agusno (Review of Primary Care Practice and Education (Kajian Praktik dan Pendidikan Layanan Primer), 2019)
Background: The use of masks affects doctor and patient communication verbally and nonverbally.Objectives: This study aims to describe the patients’ acceptance of the use of surgical masks by doctors in the patient's hearing, trust, and closeness.Methods: The research used qualitative design with phenomenological approach. In-depth interviews were conducted with 18 outpatients. Data were analyzed by content analysis.Results: Patient acceptance will be good when patients have the concept that masks are worn as a uniform and according to rules to prevent disease transmission. The use of masks does not affect the closeness and trust of patients even though they reduce hearing ability of patients, especially elderly patients. Still, they do not always ask the doctor about what is unclear. Some patients consider masks to be useful for preventing smelling of patients.Conclusions: The use of masks by doctors is acceptable to patients, does not affect the trust and closeness of patients even though it reduces hearing ability in certain patients.